Managing the menopause - Briggs, Paula 1964-; Kovacs, Gabor 1947 April 6-; Panay, Nicholas (Cambridge University Press, 2020)
With up to 60 per cent of women experiencing both physical and emotional symptoms during the menopause, including hot flushes, mood swings and loss of libido, managing these symptoms can be a complex task. Managing the Menopause is a highly practical, evidence-based reference, covering all forms of management in detail. Providing guidance on prescribing, as well as the advantages and disadvantages of various products and therapies, particular emphasis is given to addressing concerns over the long-term complications of Menopausal Hormone Therapy (MHT) use. The book contains new chapters on nutrition, ovarian tissue cryopreservation and migraine in the menopause and previous chapters have been fully updated to inform readers of the latest research. Treatment plans are included in the text, helping clinicians to support their patients quickly and effectively. A comprehensive review of the menopause that is easily understood at all levels, this is an essential guide for clinicians.